2005
DOI: 10.1183/09031936.05.00069304
|View full text |Cite
|
Sign up to set email alerts
|

Blunted    T-lymphocyte response in chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is characterised by an excessive inflammatory response to inhaled particles, mostly tobacco smoking. Although inflammation is present in all smokers, only a percentage of them develop COPD. T-lymphocytes are important effector and regulatory cells that participate actively in the inflammatory response of COPD. They comprise the T-cell receptor (TCR)-ab (CD4+ and CD8+) and TCR-cd T-lymphocytes. The latter represent a small percentage of the total T-cell population, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
(32 reference statements)
6
31
0
Order By: Relevance
“…The present results are in agreement with study of LEE et al [18], which demonstrated decreased CD4+CD25+ Treg cell number in lung tissue from emphysema patients, which in turn correlated with FOXP3 mRNA expression. This pattern of FOXP3-positive Treg cells response in small airways of COPD patients is in fact very similar to that of cd T-lymphocytes obtained from bronchoalveolar lavage fluid, which is another subpopulation of T-lymphocytes involved in tissue repair [26]. Furthermore, as illustrated in an animal model, Treg lymphocytes knockout mice (characteristics of this T-cell subset are strikingly similar between mouse and man) exhibit markedly increased inflammatory responses [27].…”
Section: Discussionmentioning
confidence: 81%
“…The present results are in agreement with study of LEE et al [18], which demonstrated decreased CD4+CD25+ Treg cell number in lung tissue from emphysema patients, which in turn correlated with FOXP3 mRNA expression. This pattern of FOXP3-positive Treg cells response in small airways of COPD patients is in fact very similar to that of cd T-lymphocytes obtained from bronchoalveolar lavage fluid, which is another subpopulation of T-lymphocytes involved in tissue repair [26]. Furthermore, as illustrated in an animal model, Treg lymphocytes knockout mice (characteristics of this T-cell subset are strikingly similar between mouse and man) exhibit markedly increased inflammatory responses [27].…”
Section: Discussionmentioning
confidence: 81%
“…They pointed out a need for follow-up of these children to assess the possible health implications of their findings. Therefore, since the distribution of TCR can vary according to age and genetic factors, the correlation between PCB and TCR found in our exposed workers seems to indicate a stimulation of the specific expression of TCR a-~involved in lymphocyte antigen recognition (23). On the contrary, the results of the study seem to exclude a direct effect of smoke and alcohol on TCR a-~and y-8 cells , in contrast with findings of some authors reporting an effect of smoke on TCR y-8 cells in humans and in mice (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since the distribution of TCR can vary according to age and genetic factors, the correlation between PCB and TCR found in our exposed workers seems to indicate a stimulation of the specific expression of TCR a-~involved in lymphocyte antigen recognition (23). On the contrary, the results of the study seem to exclude a direct effect of smoke and alcohol on TCR a-~and y-8 cells , in contrast with findings of some authors reporting an effect of smoke on TCR y-8 cells in humans and in mice (23,24). More intriguing and original, in PCB exposed subjects, is the relative % reduction of TCR y-8 T cells, in human particularly present in epithelia, both in the peripheral blood on the number of cigarettes smoked per day confirms the immunomodulating action of tobacco smoking that has already been reported by other authors, who found a greater and significant increase of Treg in bronchial alveolar lavage (BAL) of healthy smokers as compared to non-smokers/ex-smokers/smokers with chronic obstructive pulmonary disease (COPD) (9,10,30).…”
Section: Discussionmentioning
confidence: 99%
“…Subset analysis has shown a slight increase in CD4+ cells expressing interferon (IFN)-c and a decrease in cells expressing IL-4, indicating Th1 predominance in the peripheral circulation, with no changes in CD8+ cell subsets [55]. Circulating cd T-cells are increased in normal smokers but not in COPD patients [56].…”
Section: Lymphocytesmentioning
confidence: 99%